2021
DOI: 10.26418/jeep.v2i2.45516
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Rosetta Stone Language Learning Software in Teaching Listening: Documentary Research

Abstract: This study focused on analyzing the use of Rosetta Stone Language Learning Software in teaching listening comprehension. Based on three previous journal from different universities in Indonesia the writer found that selected institutional repository website in Indonesia discusses about using Rosetta Stone Language Learning Software in teaching listening comprehension. The data described the facts on the use of Rosetta Stone based on the results of research by three researchers which have been published in thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 0 publications
2
10
0
Order By: Relevance
“…Rosetta stone software also fosters students' interest in reading when participating in the learning process. Consistent with what Kurniawan et al (2021) said that learning media can do more than can be implemented, such as arousing students' curiosity or interest in reading. Rosetta stone software media applied in elementary schools can stimulate curiosity to acquire new knowledge.…”
Section: Learning Media Utilizationsupporting
confidence: 64%
“…Rosetta stone software also fosters students' interest in reading when participating in the learning process. Consistent with what Kurniawan et al (2021) said that learning media can do more than can be implemented, such as arousing students' curiosity or interest in reading. Rosetta stone software media applied in elementary schools can stimulate curiosity to acquire new knowledge.…”
Section: Learning Media Utilizationsupporting
confidence: 64%
“…The Sixth research in Indonesia (Kurniawan, Bunau, & Wardah, 2021), Rosetta Stone's Research on Students' Listening Ability. In that study it can be concluded that the Rosetta Stone software is useful for improving students' listening comprehension skills.…”
Section: Resultsmentioning
confidence: 99%
“…With Dynamic Immersion, the students will be bounded with words, images, and the voices of native speakers. (Kurniawan & Wardah, 2021).…”
Section: Diagram 1 Types Of Applications Used By the Studentsmentioning
confidence: 99%
“…Listening is one of crucial language skill that should be mastered in every language class, including English. It is one of the main thing in learning languages and it is very significant in language learning because the activity is related to listening to the sound that received by our ears (Kurniawan & Wardah, 2021). The activities in listening should be supported by media, one of the media can be in form of language learning applications on mobile phones.…”
Section: Introductionmentioning
confidence: 99%